Racial awareness: effects on justice perceptions and trust in management in the USA. Issue 1 (9th February 2015) - Buttner, E. Holly; Lowe, Kevin B.
Abstract : Purpose: – The purpose of this paper is to investigate the effects of the socio-demographic diversity characteristic, racioethnicity, vs the deeper-level socially constructed attribute, awareness of racial privilege (which the authors termed "racial awareness"), on perceptions of organizational justice and on trust in management (TM) (trust) in a US context. The authors predicted that racial awareness would have a greater effect on perceptions of interactional and procedural justice and on trust than would participant racioethnicity. Second, the authors predicted that justice perceptions would influence trust. Finally the authors predicted that justice perceptions would mediate between racial awareness and TM. Design/methodology/approach: – The authors surveyed Black, Hispanic and Native American professionals in one industry in the USA. The authors employed regression and bootstrap analyses to test the hypotheses. Findings: – Racial awareness influenced justice ratings and TM. Justice perceptions influenced employee trust. Interactional and procedural justice had indirect effects on the relationship between racial awareness and trust, supporting the hypotheses. Research limitations/implications: – Respondents were primarily African-American, so additional research to assess attitudes of other groups is needed. Respondents belonged to a minority networking group which provided the sample. It is possible that their membership sensitized the respondents to racial issues. Practical implications: – The finding suggest that managers can positively influence US minority employees' trust regardless of the employees' racial awareness by treating them with dignity and respect and by ensuring fairness in the application of organizational policies and procedures. Originality/value: – This study examined the impact of US minority employee racial awareness on justice perceptions and TM, important variables in the employer-employee relationship. Findings indicated that racial awareness was a better predictor of employee attitudes than was racioethnicity.